DISTRIBUSI BINOMIAL SEBAGAI ESTIMASI PROBABILITAS KESUKSESAN PADA UJI COBA KUALITAS LAYANAN SISTEM INFORMASI - Diana, Diana (JURNAL ILMIAH MATRIK, 2017)
The objective of the research is to implement binomial distribution to estimate the probability of success in the trial of service quality of information system using variables that exist in E-ServQual model. Binomial distribution can model the number of successes on the number of samples n of the population N, by doing n times experiment and there are only two possibilities that are successful / fail. The instrument used is a questionnaire on a linkert scale. The results of this study were p(very satisfied) = 0.288, p(satisfied) = 0.425, p(quite satisfied) = 0.18, p(not satisfied) = 0.072 and p(very unsatisfied) = 0.035. The results of the tests with the variation of the values of n and x result in the fact that small sample quantities and large probability values will increase the probability of success to be obtained. Keywords: probability, binomial distribution, software testing, service quality